Implementation of User Centered Design on Interface Design for Mental Health Selfcare Services - Rizky Wira Pranata; Anisa Herdiani; Aristyo Hadikusuma (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Mental health is essential in performing maximum activities. During the COVID-19 pandemic that is spreading all over the world. Some activities are transformed into a new activity called "New Normal". With these new activities, the level of mental health in Indonesia has deteriorated. WHO as a world health organization made a mental health pyramid that handling of every level of mental health. There are 4 levels, which are promotive, preventive, monitoring and identifying psychosocial services, and specialist services. In the results of observations and analysis, digital-based services in Indonesia prioritize levels 3 and 4, while levels 1 and 2 are still infrequent, and the application is still not perfectly weighted. This study will design a mental health application by emphasizing level 1 and 2 treatment, namely self-care and storytelling sessions using the User Centered Design method, and the results of the evaluation used the usability testing method and the usability scale system. With this research, potential users obtain an interface resolution with a mood tracker, self-care, and storytelling features that users desire. By helping the user to perceive the history of the condition, getting self-care and storytelling rooms according to the user's condition, and helping the user's condition to bolster up and not add to the burden of the user's condition. The outcome of the evaluation that has been done, results that the average user completed each task for 16.59 seconds, the average result is 0 miss click and 0 miss click page, and the results from the System Usability Scale are 81.51 with the "Excellent" category, with the composition of solutions provided to answer user problems.